Kredyt kupiecki w teoriach struktury kapitału w warunkach finansowania małego przedsiębiorstwa - Zawadzka, Danuta (Trade Credit in the Capital Structure Theories in the Conditions of Small Company Financing, 2008)
The aim of the paper is to evaluate the assumptions of capital structure theories with reference to trade credit, in the conditions of small companies financing. The initial analysis of Bankruptcy Theory, Agency Theory and Pecking Order Theory as a consequence of informational asymmetry and transaction costs, in the context of trade credit, is presented in the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 638-644